Drip water analysis of site 1A, 1IV, 2B and 2E from the Golgotha Cave in southwest Western Australia - Treble, Pauline C; Baker, Andy; Hellstrom, John C; Abram, Nerilie J; Crawford, Jagoda; Gagan, Michael K; Borsato, Andrea; Griffiths, Alan D; Bajo, Petra; Markowska, Monika; Priestley, Stacey; Hankin, Stuart I; et al. (PANGAEA, 2022)
Dripwater was collected every 4-6 weeks from Golgotha Cave (34.1°S, 115.1°E) in southwest Western Australia from 2005 until 2019, although beginning in 2008 for site 2E and in 2013 for site 1IV. Cave location is rounded to nearest tenth of a degree as exact locations not disclosed for cave conservation purposes. Dripwaters were collected for paleoclimate and paleohydrology studies. Data from August 2005 until March 2012 were previously published in Treble et al. (2013) and the longer dataset in Treble et al (2021). Please cite Treble et al. (2013, 2021) when using these data. Dripwaters were collected at 4-6 week intervals from bulk 1 L high-density polyethylene collection vessels, fitted with funnels, that were emptied following collection of water for analyses. Drip rates were manually timed during each collection visit. The drip sites pair with stalagmites collected from these locations as follows: site 1A (GL-S1), site 1IV (GL-S4), site 2B (GL-S2), site 2E (GL-S3). Stable water isotopes (δ18O and δ2H) collected between August 2005 and April 2011 were determined by: 1. offline equilibration technique at the Research School of Earth Sciences, Australian National University; 2. using an LGR-24 d cavity ringdown mass spectrometer at the University of New South Wales for samples from May 2011-March 2012; and 3. using Picarro L2120-I Water Analyser at ANSTO from 2012 onwards. Analytical error all techniques was 0.1 ‰ (1 s.d.; calculated from within-run internal references materials). See citations in Treble et al. (2013) for details of methods. Golgotha Cave is located in Eucalyptus forest with dense understorey in the Leeuwin-Naturaliste National Park. The hostrock is Quaternary aeolinite and the soil thickness is variable with measurements ranging from 0.3 – 3 m deep. The cave entrance is 70 m above sea level. Dripwater sites 1A, 1IV are located approximately 60 m from the entrance where the limestone thickness overhead is 30 m while dripwater sites 2B and 2E are located approximately 90 m from the entrance where the limestone thickness overhead is 40 m. Mean annual site temperature is 15.6 ±0.5°C and mean annual rainfall is 1101±157 mm (1911-2018 period; Australian Bureau of Meteorology AWRA-L dataset http://www.bom.gov.au/water/landscape. Inside the cave, temperature ranges from 14.5-14.8°C, windspeed is low (≤0.03 m s-1) and relative humidity ranges from 98-100% (Treble et al 2019). Rainfall water isotope measurements from Calgardup Cave, located 5 km from Golgotha Cave and complimentary to this dataset, are available from the IAEA Water Isotope System for data analysis, visualization and Electronic Retrieval, https://nucleus.iaea.org/wiser/ using station code 9564101.
Keywords: cave monitoring; dripwater; water isotopes; Western Australia